Is There a Relationship between the Staining Pattern of Classical Neuroendocrine Markers and Clinicopathological Findings in Neuroendocrine Tumors of the Appendix? - Merve CİN; Enver YARIKKAYA; Selçuk CİN; Özgecan GÜNDOĞAR (Bezmiâlem Science)
Objective: This study investigates the association between staining patterns of classical neuroendocrine markers, synaptophysin (Snp) and chromogranin-A (Chr), and clinicopathological findings in appendiceal neuroendocrine tumors (NETs). These tumors, often diagnosed incidentally post-appendectomy, pose diagnostic challenges due to their diverse histomorphologic patterns. The study aims to enhance understanding of the relationship between staining patterns and key pathological parameters. Methods: A retrospective analysis included 28 cases of appendiceal NETs diagnosed over an 8-year period. Histopathological features, including grade, lymphovascular invasion, stage, localization, size, Ki67 proliferation index, and morphological pattern, were reassessed. Immunohistochemical staining of Snp and Chr was examined for extensity and intensity in NET areas. Results: The study comprised 17 female and 11 male patients, with a mean age of 34 years. Histomorphological patterns included small nests, large nests, and trabecular-palisading patterns. Statistically significant correlations were observed between Snp staining intensity and tumor size, and Chr staining extensity and histomorphologic patterns. Chr staining extensity exceeding 95% was identified in all cases with large nest patterns. Additionally, Chr staining extensity increased with advancing pathological stage, notably between pT1-pT4 groups. Conclusion: This study emphasizes the importance of immunohistochemical evaluation, particularly in distinguishing between L and EC cells in appendiceal NETs. The unique trabecular-palisading pattern, associated with L cell histomorphology, demonstrated significant correlations with Chr staining patterns. Snp staining intensity correlated with tumor size, while Chr staining percentage increased with advanced pathological stages. The findings suggest that it will create awareness in pathology practice in terms of both diagnosis and pathological prognostic parameters (tumor size, stage).